2023
DOI: 10.3389/fmicb.2022.1012512
|View full text |Cite
|
Sign up to set email alerts
|

Linkages between the molecular composition of dissolved organic matter and soil microbial community in a boreal forest during freeze–thaw cycles

Abstract: Soil dissolved organic matter (DOM) plays a vital role in biogeochemical processes. Global warming leads to increased freeze–thaw cycles (FTCs) in boreal forest soils, which can change DOM production and consumption. However, the interactions between the chemical composition of DOM molecules and the microbial communities that drive C decomposition in the context of freeze–thaw are poorly understood. Here, a FTCs incubation experiment was conducted. Combined with pyrolysis gas chromatography–mass spectrometry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…The effect of FTC on DOM mobilisation has been highlighted also in more recent studies, (e.g., Speetjens et al, 2022;Yang et al, 2023). Moreover, these studies suggest that the altered composition of DOM, influenced by changes in soil microbial activity due to freeze-thaw cycles (Feng et al, 2007;Yang et al, 2023), has the potential to shift the optical properties of DOM and increase its humification index (Speetjens et al, 2022). This phenomenon underscores the intricate relationship between climate-induced freeze-thaw dynamics and the composition of dissolved organic matter, most likely impacting the water optical properties observed in the Gulf of Riga over the past two decades.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The effect of FTC on DOM mobilisation has been highlighted also in more recent studies, (e.g., Speetjens et al, 2022;Yang et al, 2023). Moreover, these studies suggest that the altered composition of DOM, influenced by changes in soil microbial activity due to freeze-thaw cycles (Feng et al, 2007;Yang et al, 2023), has the potential to shift the optical properties of DOM and increase its humification index (Speetjens et al, 2022). This phenomenon underscores the intricate relationship between climate-induced freeze-thaw dynamics and the composition of dissolved organic matter, most likely impacting the water optical properties observed in the Gulf of Riga over the past two decades.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, the greatest FTC effect has been observed at mild frost conditions. The effect of FTC on DOM mobilisation has been highlighted also in more recent studies, (e.g., Speetjens et al, 2022;Yang et al, 2023). Moreover, these studies suggest that the altered composition of DOM, influenced by changes in soil microbial activity due to freeze-thaw cycles (Feng et al, 2007;Yang et al, 2023), has the potential to shift the optical properties of DOM and increase its humification index (Speetjens et al, 2022).…”
Section: Discussionmentioning
confidence: 77%
“…F420 is a co-enzyme that is costly to synthesize; nevertheless, Ney et al [89] found that it was commonly synthesized by aerobic bacteria. Meanwhile, coenzyme M is found in methanotrophic archaea and used by bacteria in metabolizing of different substrates, for example alkenes [90], which are found in boreal forest soils [91]. More interestingly, alkenes are known to be produced by bacteria associated with lichens [92].…”
Section: Bacterial Metabolic Potential Differs In Green and Brown Gam...mentioning
confidence: 99%
“…The effect of FTC on DOM mobilisation has been highlighted also in more recent studies, (e.g., Speetjens et al, 2022;Yang et al, 2023). Moreover, these studies suggest that the altered composition of DOM, influenced by changes in soil microbial activity due to freeze-thaw cycles (Feng et al, 2007;Yang et al, 2023), has the potential to shift the optical properties of DOM and increase its humification index (Speetjens et al, 2022). This phenomenon underscores the intricate relationship between climate-induced freeze-thaw dynamics and the composition of dissolved organic matter, most likely impacting the water optical properties observed in the Gulf of Riga over the past two decades.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, the greatest FTC effect has been observed at mild frost conditions. The effect of FTC on DOM mobilisation has been highlighted also in more recent studies, (e.g., Speetjens et al, 2022;Yang et al, 2023). Moreover, these studies suggest that the altered composition of DOM, influenced by changes in soil microbial activity due to freeze-thaw cycles (Feng et al, 2007;Yang et al, 2023), has the potential to shift the optical properties of DOM and increase its humification index (Speetjens et al, 2022).…”
Section: Discussionmentioning
confidence: 77%